DAMPAK PERNIKAHAN DINI MENURUT PERSFEKTIF ISLAM - Mardiyana Harahap; Zaianal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
Marrriage is the initial process of forming a harmonious family. However, marriage also Marriage requires preparation and conditions so that problems do not arise in the future. One of them concerns the issue of age or what is called Early Marriage. Early Marriage is controversial among society because each perspective has a different view. The impact of early marriage is not only a high divorce rate due to incompatibility between partners, but also domestic violence (KDRT), infidelity, and complications that occur during pregnancy which causes a high risk of maternal and child mortality. In the Islamic view, early marriage can have a positive impact, namely preventing adultery. According to the view of the Shafi'i School, a marriage can be carried out if the bride is of age and her parents ask for their daughter's consent so that there is no feeling of coercion when the marriage takes place. This can be used as a reference for parents who want to marry off their children even though they are still at an early age. Not only parents, but teenagers who want to get married at a young age also need to think about and prepare for all possibilities so that problems do not occur that cause the breakdown of a household.